Artificial Intelligence in Sustainable Finance: Mapping ESG Integration ‎and Risk Detection Frameworks - Omar , Boutahir; Habiba, Lahlou-Kassi (International Journal of Accounting and Economics Studies, 2025)
This systematic review explores how Artificial Intelligence (AI) is being incorporated into ‎sustainable investment practices, with a particular focus on its influence on decision-making ‎processes, risk assessment, and the enhancement of environmental, social, and governance ‎‎(ESG) outcomes. Drawing on 40 peer-reviewed studies published between 2018 and 2025, the ‎review synthesizes the evolution of AI applications in responsible finance and identifies five ‎major research clusters: (1) AI-driven ESG performance and sustainable finance integration, (2) ‎AI, FinTech, and blockchain innovation for green finance, (3) AI-enhanced risk detection and ‎financial resilience, (4) systematic and theoretical foundations of AI in sustainable finance, and ‎‎(5) ethical, governance, and responsible AI frameworks.‎Findings reveal that machine learning, natural language processing, and big data analytics are ‎increasingly used to evaluate ESG indicators, optimize investment strategies, and improve ‎transparency in sustainability reporting. However, several challenges persist, including ‎algorithmic bias, data heterogeneity, limited model interpretability, and the absence of ‎standardized ESG metrics. These limitations highlight the need for greater model transparency, ‎ethical accountability, and interdisciplinary collaboration between data scientists, financial ‎practitioners, and policymakers.‎The review is framed by theoretical perspectives, including the Resource-Based View and ‎Responsible AI frameworks, to contextualize AI’s role in sustainable investment. Also, this review ‎demonstrates that AI is not merely a technological tool but a transformative driver of sustainable ‎investment practices. By fostering responsible innovation, improving data reliability, and ‎supporting evidence-based decision-making, AI has the potential to build a more transparent, ‎resilient, and inclusive financial ecosystem, accelerating the global transition toward sustainable ‎development‎.
Keywords: Artificial Intelligence; Sustainable Investment; Green Finance; ESG; Risk Management